The inclusion of ethnic-racial differences and gender diversity in the educational political agenda (Research, Society and Development, 2022)
School practice involves all the confrontations of the society in which the school is inserted. Everything that is present in society reflects in the school, such  as racism, homophobia, multiculturalism, social difference and others, which, in turn, leads us to aim for a resignification of education and school, in a bias of going beyond the reflection of social issues, seeking a greater inclusion of diversities in the school agenda. This paper aims to address school practice with a focus on ethnic-racial differences and gender diversity. From a bibliographic research, of exploratory nature, the theme is worked on the perspective that the integrated and humanized school can be the way for these challenges to be seen as student growth in overcoming them and promoting a more just and egalitarian society. The vision of being human is that of a singular subject, who permanently self-constructs, thinks and acts with ethical options and values, thus building possibilities for a better and quality life.